Evolution of the Model of the Clinical Practice of Emergency Medicine: 1979 to Present. (2nd February 2017) - Counselman, Francis L.; Beeson, Michael S.; Marco, Catherine A.; Adsit, Susan K.; Harvey, Anne L.; Keehbauch, Julia N.
Abstract: The Model of the Clinical Practice of Emergency Medicine (the EM Model) is a three‐dimensional representation of the clinical practice of emergency medicine. It is a product of successful collaboration involving the American Board of Emergency Medicine (ABEM), the American College of Emergency Physicians (ACEP), the Society for Academic Emergency Medicine (SAEM), the Emergency Medicine Residents' Association (EMRA), the Council of Emergency Medicine Residency Directors (CORD), the Residency Review Committee for Emergency Medicine (RRC‐EM), and the American Academy of Emergency Medicine (AAEM). In 2017, the most recent update and revision of the EM Model will be published. This document will represent the culmination of nearly 40 years of evolution, from a simple listing of presenting patient complaints, clinical symptoms, and disease states into a three‐dimensional representation of the clinical practice of emergency medicine. These dimensions include conditions and components, physician tasks, and patient acuity. In addition, over the years, two other documents have been developed, the Knowledge, Skills, and Abilities (KSAs) and the Emergency Medicine Milestones. Both serve as related and complementary educational and assessment tools. This article will review the development of the EM Model from its inception in 1979 to today.